Evaluasi Penyaluran Dana Zakat Pada Program Pendidikan Baznas Pusat - Nubdzatus Saniyah; Cecep Castrawijaya (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2019)
BAZNAS was formed by Republic of Indonesia's Presidential Decree No. 8 of 2001, which is a non-structural and independent Government institution. This institution is responsible to the President and authorized to carry out the task of managing zakat nationally. In particular, BAZNAS has the mandate to distribute zakat funds to those who need them, especially those who need educational assistance and get their share. In addition, BAZNAS also has responsibilities in each of its programs to fit the expected goals. Based on the background, the authors pay attention to the importance of evaluations in carrying out the distribution of zakat funds for educational programsconducted by the National BAZNAS in Indonesia. The problems that will be studied are the mechanism for distributing zakat funds at the central BAZNAS in the field of education, the distribution pattern of the central BAZNAS zakat fund in the field of education, and the evaluation of the implementation of zakat funds at the Central BAZNAS in the field of education. The research that the authors conducted was to use a qualitative approach with a cycle that began with the selection of problems, followed by making questions, making notes or recording at the interview and then analyzing.The results of this studyare that the authors can seek the procedure for obtaining educational assistance in accordance with applicable provisions, so that the funds distributed can be channeled to those who really need it. The pattern of distribution of zakat funds in the education sector is divided into two parts, namely distribution and utilization. The evaluation model used by BAZNAS indirectly uses the CIPP evaluation model (Context, Input, Process, Product). It is because evaluation conducted by BAZNAS has targets, opportunities and results of achievement. The distribution of BAZNAS zakat funds in the education sector in 2016 amounted to Rp. 8,070,388,736 with a percentage of 0.96% and 1,166 beneficiaries of beneficiaries. Whereas in 2017 there was an increase of 20% with a nominal value of Rp. 25,518,460,752 and percentage of 2.71% and 21,181 beneficiaries directly and 3,051 indirect beneficiaries.